Activity Based Costing (ABC) Di Industri Manufaktur: Tinjauan Literatur Tentang Efisiensi dan Kinerja Di Berbagai Negara - Agnes Fanny Laurent; Agus Munandar (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study analyses the application of the Activity-Based Costing (ABC) system in the manufacturing sector with the main objective of improving the efficiency and effectiveness of company operations compared to conventional cost accounting approaches. The ABC method links costs with relevant activities, thus giving a more realistic cost allocation that assists firms in identifying their inefficient costs and improves the quality of managerial decisions. This research applies the SLR approach in identifying, evaluating, and summarizing findings from various studies on ABC implementation. The search process has been carried out through the Google Scholar database, while the period of search concern is 2019 - 2024. Therefore, from the initial outcome of 588 articles retrieved, only 31 articles with the inclusion requirements were selected to be analyzed in depth. The findings show that companies using the ABC method have superior financial performance and competitiveness compared to those using traditional methods. Although the implementation of ABC requires a significant initial investment, the long-term benefits in the form of efficiency and more optimal resource management contribute greatly to the sustainability of manufacturing companies in the global market.